2013
DOI: 10.1111/joop.12042
|View full text |Cite
|
Sign up to set email alerts
|

Student‐recruited samples in organizational research: A review, analysis, and guidelines for future research

Abstract: Student‐recruited sampling, a technique involving the use of student recruiters to find participants on behalf of a researcher, has been increasingly used in organizational research; yet there has been little attempt to understand its implications for the conclusions scholars draw from research. In this study, we meta‐analyse studies of engagement and perceptions of politics in order to examine whether student‐recruited sampling leads to samples that differ from other samples and whether those differences resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
212
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(237 citation statements)
references
References 262 publications
(60 reference statements)
5
212
1
4
Order By: Relevance
“…Of course, our sample may be different from a representative sample in other characteristics, which could have affected the findings in an unknown way. A recent meta-analysis by Wheeler, Halbesleben, Shanine, and Donovan (2012), however, showed that correlations from snowball samples were only slightly smaller than those from nonsnowball samples, suggesting that if anything, our results provide a conservative estimate of stressor-CWB relationships. Nevertheless, future research on reciprocal effects of work stressors and CWB would benefit from using probability samples.…”
Section: Limitationscontrasting
confidence: 66%
“…Of course, our sample may be different from a representative sample in other characteristics, which could have affected the findings in an unknown way. A recent meta-analysis by Wheeler, Halbesleben, Shanine, and Donovan (2012), however, showed that correlations from snowball samples were only slightly smaller than those from nonsnowball samples, suggesting that if anything, our results provide a conservative estimate of stressor-CWB relationships. Nevertheless, future research on reciprocal effects of work stressors and CWB would benefit from using probability samples.…”
Section: Limitationscontrasting
confidence: 66%
“…However, recent meta-analytic findings (Wheeler et al, 2014) suggest slightly lower effect sizes and correlations in convenience samples compared to non-convenience samples, whereas the same overall conclusions could be drawn from both samples. Hence, the use of a convenience sample would have resulted in more conservative estimates of the relationships between the variables under study.…”
Section: Discussionmentioning
confidence: 85%
“…Student‐recruited sampling has become an acceptable research design feature, especially when collecting survey data (Demerouti & Rispens, ; Hochwarter, ). Wheeler et al () provide a recent meta‐analysis of engagement studies, which did not find a significant difference in the observed relationships found in studies based on their use of traditional or student‐recruited sampling.…”
Section: Methodsmentioning
confidence: 97%